Glass fiber–reinforced, bio-based poly(trimethylene terephthalate) for extrusion. Issue 4 (December 2013) - Ren, Yu; Gavenonis, John; Ai, Rina; Huang, Ray; Chervin, Christophe; Tang, Yanshou; Zhang, Jane; Qian, Jack; Yang, Gaopin; Yu, Ting; Ankrom, Linda S.
Abstract : Sorona ® EP poly(trimethylene terephthalate) (PTT) is an engineering thermoplastic resin that contains 37% bio-based content derived from its 1, 3-propanediol monomer and is a commercially successful product for fiber and injection molding applications. This contribution describes the development of PTT formulations for extruded tubes. PTT compositions containing glass fiber (GF) reinforcement and reactive impact modifier were formulated to produce tubes with 63- and 110-mm outer diameters and 5- and 10-mm wall thicknesses. Compositions with ≥30% GF and ≥10% reactive impact modifier yielded continuous tubes with consistent wall thicknesses and excellent surface appearances. The physical properties of the resulting tubes make them attractive for a number of end-use applications in the electrical and electronic, water management, oil and gas and other industries.